The Predictors of Conduction Disturbances Following Transcatheter Aortic Valve Replacement in Patients With Bicuspid Aortic Valve: A Multicenter Study - Guo, Yuchao; Zhou, Dao; Dang, Mengqiu; He, Yuxing; Zhang, Shenwei; Fang, Jun; Wu, Shili; Huang, Qiong; Chen, Lianglong; Yuan, Yiqiang; Fan, Jiaqi; Jilaihawi, Hasan; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: To evaluate the predictors of NOCDs in bicuspid aortic valve (BAV) patients using self-expandable valve (SEV) and identify modifiable technical factors to reduce risks of NOCDs. Background: New-onset conduction disturbances (NOCDs), including complete left bundle branch block (CLBBB) and high-grade atrioventricular block (HAVB), remain the most common complication after transcatheter aortic valve replacement (TAVR). Methods: A total of 209 consecutive BAV patients who underwent self-expanding TAVR in 5 centers in China were enrolled from Feb 2016 to Sep 2020. The optimal cut-offs in this study were generated from ROC analyses. Results: Forty-two (20.1%) patients developed CLBBB and 21 (10.0%) patients developed HAVB after TAVR, while 61 (29.2%) patients developed NOCDs. Coronal MS <4.9mm (OR: 3.08, 95%Confidence Interval [CI]: 1.63-5.82, p = 0.001) or infra-annular MS length <3.7 mm (OR: 2.18, 95%CI: 1.04-4.56, p = 0.038) and LVOT perimeter <66.8 mm, (OR: 4.95 95%CI: 1.59-15.45, p = 0.006) were powerful predictors of NOCDs. The multivariate model including age >73 years (OR: 2.26, 95%CI: 1.17-4.36, p = 0.015), Δcoronal MSID <1.8 mm (OR: 7.87, 95%CI: 2.84-21.77, p <0.001) and oversizing by LVOT perimeter >3.2% (OR: 3.42, 95%CI: 1.74-6.72, p <0.001) showed best predictive value of NOCDs, with c-statistic = 0.768 (95%CI: 0.699–0.837, p <0.001). The incidence of NOCDs was much lower (7.5% vs. 55.2%, p <0.001) in patients without Δcoronal MSID <1.8 mm and oversizing by LVOT perimeter >3.2% compared with patients who had these two risk factors. Conclusion: The risk of NOCDs in BAV patients could be evaluated before TAVR procedure based on MS length and LVOT perimeter. Implantation depth should be guided by MS length and reducing the oversizing ratio was a feasible strategy for patients with short MS length.